2011
DOI: 10.5137/1019-5149.jtn.3696-10.3
|View full text |Cite
|
Sign up to set email alerts
|

Subdural hematoma associated with skull and dural metastasis of gastric carcinoma. a case report

Abstract: Skull bone metastasis from the gastric cancer is a rare. We reported a 52-year-old male proven to have stomach cancer and who underwent subtotal gastrectomy 5 months previously. Within the past 2 weeks, he experienced headache and dizziness followed by weakness of the left lower limb. A diagnosis of right chronic subdural hematoma (SDH) was made, and a burr hole was performed for drainage of the hematoma. However, 5 days later, the patient had sudden loss of consciousness without external evidence of trauma to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Our case differs from previously reported cases of gastric adenocarcinoma with dural metastases [4][5][6][7][8][9][10][11][12][13] (Table 1). First, the original SDH was a pachymeningeal en plaque tumor.…”
Section: Observationscontrasting
confidence: 99%
“…Our case differs from previously reported cases of gastric adenocarcinoma with dural metastases [4][5][6][7][8][9][10][11][12][13] (Table 1). First, the original SDH was a pachymeningeal en plaque tumor.…”
Section: Observationscontrasting
confidence: 99%
“… 12 17) Also, many case reports showed a relationship between brain metastasis of malignant neoplasm and CSDH. 1 8 10 16) Authors suggested a multifactorial pathogenesis of CSDH in malignancy such as dural vessel occlusion and rupture by tumor cells, tumor necrosis and chemotherapy-induced thrombocytopenia or disseminated intravascular coagulation secondary to an underlying malignancy. 11) Authors suggested that CSDH seems easily to occur in patients with malignant neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, there were no significant signs of disseminated intravascular coagulation (DIC) and no major coagulation problems. Retrograde seeding by the valveless vertebral venous system (Barton’s plexus) has been thought to be a cause for bone and dural metastasis from prostate carcinoma [ 10 ].…”
Section: Discussionmentioning
confidence: 99%